2008
DOI: 10.1021/bi702059f
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed Mutations at D1-Thr179 of Photosystem II in Synechocystis sp. PCC 6803 Modify the Spectroscopic Properties of the Accessory Chlorophyll in the D1-branch of the Reaction Center

Abstract: D1-Thr179, which overlies the reaction center chlorophyll Chl D1 of Photosystem II was replaced with His and Glu through site-directed mutation in Synechocystis sp. PCC 6803. Spectroscopic characterization of the mutants indicates that, compared to wild type, the main bleaching in the triplet-minus-singlet absorbance difference spectrum and the electrochromic band shift in the (P680 (+)Q A (-)-P680Q A) absorbance difference spectrum are displaced to the red by approximately 2 nm in the D1-Thr179His mutant and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
59
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 62 publications
(144 reference statements)
20
59
0
Order By: Relevance
“…[20]). From calculations of Q A À Car + ÀQ A Car optical difference spectra and comparison with experimental data, it can be concluded that only Car D2 and not Car D1 is involved in secondary electron transfer in PS-II [34] (Figure 11). The linear dichroism of the absorbance band of the Car cation around 1000 nm shows that the oxidized Car is oriented parallel to the membrane plane, [65] which supports the assignment that Car D2 is oxidized by P 680 + .…”
Section: Pathways Of Secondary Electron Transfermentioning
confidence: 97%
See 2 more Smart Citations
“…[20]). From calculations of Q A À Car + ÀQ A Car optical difference spectra and comparison with experimental data, it can be concluded that only Car D2 and not Car D1 is involved in secondary electron transfer in PS-II [34] (Figure 11). The linear dichroism of the absorbance band of the Car cation around 1000 nm shows that the oxidized Car is oriented parallel to the membrane plane, [65] which supports the assignment that Car D2 is oxidized by P 680 + .…”
Section: Pathways Of Secondary Electron Transfermentioning
confidence: 97%
“…Measured TÀS spectra ( 3 PÀ 1 P) of wild-type and mutant PS-II core complexes from Synechocystis sp. PCC 6803 [33,34] (upper part) are compared with calculated spectra [35] (lower part). In the calculations of the mutant spectra, the site energy of the pigment affected by the mutation was shifted with respect to its wild-type value, as indicated in the legend of Figure 4.…”
Section: The Excited State P 680 * Of the Rc And Primary Electron Donormentioning
confidence: 99%
See 1 more Smart Citation
“…A more theoretically challenging method is to directly calculate site energies from structural data [21]. Any conclusions need to be consistent with other results available, such as the spectral effects associated with site-directed mutagenesis, which can modify the binding site associated with specific chlorophylls [22]. Recently, the two approaches of spectral modeling [23] and direct calculations [24] have been applied successfully to the CP43 protein.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the structural similarity to the purple bacteria, the special pair of chlorophyll (Chl) a (P680) was considered as a primary charge separation-site in PS II reaction center (RC) complexes that consist of the D1, D2, and cytochrome (Cyt) b 559 proteins (see review by Satoh 1993). Recently, a new mechanism has been proposed for reaction processes in PS II due to the development of biophysical measurement, in which electron transfer is initiated from the accessory Chl a D1 to pheophytin (Pheo) a, followed by hole transfer from accessory Chl a D1 to P680 (Prokhorenko and Holzwarth 2000;Frese et al 2003), and Chl a D1 accumulates a triplet state (Noguchi et al 2001;Schlodder et al 2008). The minimum unit of PS II corresponds to RC complexes that were first isolated by Nanba and Satoh from spinach (Nanba and Satoh 1987).…”
Section: Introductionmentioning
confidence: 99%